P736 Point-of-care infliximab quantification in inflammatory bowel disease in daily practice. (16th January 2018) - Costa Santos, M P; Palmela, C; Gouveia, C; Fidalgo, C; Glória, L; Cravo, M; Torres, J
Abstract: Background: Therapeutic drug monitoring (TDM) in inflammatory bowel disease (IBD) is increasingly used to guide treatment optimisation. Although debatable, an infliximab trough level (IFX-TL) of 3–7 μg/ml is commonly accepted to be within the therapeutic range during the maintenance phase. Some obstacles to TDM implementation in day-by-day use are the rather long time-to-result and the need to run samples in batches to increase cost-effectiveness, allowing therapeutic decisions to be made only in the following infusion. The new point-of-care (POC) IFX device (Quantum Blue IFX assay®) has been recently validated for IFX quantification. This method is easy to use, does not require specialised lab material or personnel and delivers results in 15 min. The aim of our study was to describe the implementation of this method in a daily practice setting. Methods: Serum samples from patients with IBD under maintenance therapy with IFX were prospectively collected within a six-month period. All measurements were conducted by the staff at the infusion centre. POC IFX-TL were determined. For the purposes of this study, IFX-TL were considered therapeutic when concentrations were between 3–7 μg/ml, infratherapeutic when < 3 μg/ml and supratherapeutic when > 7 μg/ml. Whenever IFX levels were undetectable (< 0.4 μg/ml) or < 1 μg/ml antibodies levels were determined. Demographic, clinical and laboratory data (CRP) were prospectively collected. Colonoscopies that were performed within this six-month period were also registered. Results: Thirty-eight samples were collected from 29 patients in clinical remission (25 with Cronh's disease and 4 with ulcerative colitis). There was a negative correlation between IFX-TL and CRP ( r = −0.362, p = 0.028). IFX-TL were within the therapeutic range in only 13 samples (34%), supratherapeutic in 15 (40%) and infratherapeutic in 10 (26%). In the infratherapeutic group, all patients with undetectable levels presented antibodies to IFX ( n = 8). Infratherapeutic IFX-TL were also associated with higher CRP ( p = 0.005) and with active disease at endoscopy ( p = 0.005). Conclusions: Point-of-care IFX was easy to implement on a daily clinical practice setting. IFX-TL considered to be within the therapeutic range were measured in one-third of patients. In the remaining patients an immediate treatment adjustment could have been made, allowing for resources saving.